2020
DOI: 10.1002/smj.3190
|View full text |Cite
|
Sign up to set email alerts
|

CEOdismissal: Consequences for the strategic risk taking of competitorCEOs

Abstract: We propose that CEO dismissal can change the strategic decision-making of CEOs at competing firms. Competitor CEOs will experience an increase in job insecurity, which motivates them to refrain from strategic risk taking. We also identify two key boundary conditions that shape the influence of CEO dismissal on competitor CEOs' risk taking. We test our ideas on a sample of CEO dismissals among S&P 1500 firms using a novel synthetic control method approach to matching. We also test the underlying theoretical mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
65
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(67 citation statements)
references
References 162 publications
(219 reference statements)
1
65
0
1
Order By: Relevance
“…In addition to strategic events, nonstrategic events can alter the perceptions of peer organizations’ managers, change their actions, and generate interorganizational spillover. CEOs of rival firms can reduce their risk taking following the dismissal of the CEO at a focal firm (Connelly et al, 2020). Hedge fund activism, as a nonstrategic event, can prompt effects beyond targeted firms.…”
Section: Interorganizational Spillover To Peer Organizationsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to strategic events, nonstrategic events can alter the perceptions of peer organizations’ managers, change their actions, and generate interorganizational spillover. CEOs of rival firms can reduce their risk taking following the dismissal of the CEO at a focal firm (Connelly et al, 2020). Hedge fund activism, as a nonstrategic event, can prompt effects beyond targeted firms.…”
Section: Interorganizational Spillover To Peer Organizationsmentioning
confidence: 99%
“…When peer organizations and their stakeholders are unaware of events, interorganizational spillover is unlikely to take place. As noted in our review sections, existing research has investigated a myriad of events that can trigger interorganizational spillover, including industry accidents (Barnett & King, 2008; Diestre & Rajagopalan, 2014), CEO dismissal (Burchard et al, 2020; Connelly et al, 2020), shareholder activism (Reid & Toffel, 2009; Shi et al, 2020), social activism (Briscoe et al, 2015; Fremeth et al, 2021), financial misconduct (Beatty et al, 2013; Paruchuri & Misangyi, 2015), scandals (Nalick et al, 2019; Piazza & Jourdan, 2018), disease outbreak (Paruchuri et al, 2019), protests (Ferguson et al, 2018; Piazza & Perretti, 2020), product recall (Zavyalova et al, 2012), and award events (Fremeth et al, 2021; Reschke, Azoulay, & Stuart, 2018).…”
Section: The Amc Perspective Into Interorganizational Spillovermentioning
confidence: 99%
See 1 more Smart Citation
“…Nor is dismissal well received by investors when it is viewed as premature (proactive or “too soon”), before the CEO has had a chance to enact change (Ertugrul & Krishnan, 2011). Furthermore, Connelly, Li, Shi, and Lee, (2020) found the dismissal of a CEO impacted the risk taking of other CEOs within their industry, demonstrating that the dismissal of one CEO can have ramifications for other firms as well as for the industry as a whole.…”
Section: Ceo Dismissal In the Literature: Where Are We?mentioning
confidence: 99%
“…Dismissing the CEO would certainly constitute an impactful event capable of having such spillover effects. In this vein, Connelly et al (2020) recently found that CEO dismissal at one firm induces heightened fears of job insecurity among CEOs at competing firms. Yet, whether the dismissal of a CEO at one firm actually leads to a wave of dismissals at other firms remains to be investigated.…”
Section: The Future Of Ceo Dismissal: Where Do We Go?mentioning
confidence: 99%